Asuhan Kebidanan Pada Ibu Bersalin Di PMB Nurhayati Wilayah Kerja Puskesmas Air Tiris Tahun 2022 - Anita HL, Elzuliana; Harmia, Elvira (Evidence Midwifery Journal, 2023)
Labor is where the baby, placenta, and amniotic membranes come out of the mother's uterus. Normal delivery occurs in term pregnancies with a gestational age of 37 weeks or more without any complications. Midwifery care for this mother aims to avoid failure to continue normal delivery. So that it can reduce complications that might occur in mothers who will give birth normally. With the results of Mrs.A aged 20 years P1A0H1, namely experiencing a normal delivery. During the first stage, the data obtained were the latent phase I phase and the active phase in Mrs. A occurred for approximately 13 hours. The second stage lasted for approximately 3 hours. Stage III lasts approximately 10 minutes. stage IV lasted for 2 hours after the placenta was born, with monitoring of bleeding of approximately 200 cc. So thus the authors do not find a gap between theory and facts that occur in practice